Expression of interferon-γ and its effect on cough hypersensitivity in chronic refractory cough patients. Issue 6 (7th January 2022) - Sun, Jiayang; Zhan, Chen; Deng, Zheng; Luo, Wei; Chen, Qiaoli; Jiang, Mei; Zhong, Nanshan; Lai, Kefang
Abstract : Chronic refractory cough (CRC) is characterised by cough hypersensitivity. Interferon-γ (IFN-γ) has been reported to induce calcium influx, action potentials of vagal neurons in vitro and cough response in guinea pigs. While the effect of IFN-γ in CRC patients remains unknown. Here, via flow-cytometry and inhalation cough challenge, we found CRC patients had significantly increased levels of sputum IFN-γ + CD4 + T cells, IFN-γ + CD8 + T cells as well as supernatant of IFN-γ. The average number of coughs in CRC patients increased as the concentration of inhaled IFN-γ went up in IFN-γ cough challenge. Two or more coughs and five or more coughs elicited by inhaled IFN-γ in CRC patients occurred in 7 of 10 and 2 of 10, respectively. Preinhaled IFN-γ (100 µg/mL) increased the capsaicin cough sensitivity in CRC patients but not healthy volunteers. Targeting IFN-γ may be a potential effective anti-tussive strategy in CRC patients.